2014
DOI: 10.4103/0973-1296.133299
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of gypsogenic acid isolated from Gypsophila trichotoma

Abstract: Background:Gypsophila trichotoma Wend. (Caryophyllaceae) is a medicinal plant which is protected in Bulgaria by the Biodiversity Law. Previous studies have showed the presence of triterpene saponins, sterols, flavonoids, triterpens, etc.Objective:Gypsogenic acid, isolated from Gypsophila trichotoma roots, was evaluated for cytotoxic activity.Materials and Methods:The structure of the compound was elucidated by spectral methods. The cell survival fraction was determined by the MTT dye reduction assay, performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
8
3
Order By: Relevance
“…An interesting comparison might be made between the oleananes gypsogenin ( 5 ) and gypsogenic acid ( 6 ), whose only difference is the group on C‐4: an aldehyde and a carboxylic acid, respectively (Figure 2). Gypsogenin has presented a 24‐hour IC 50 of 12.67 μM against K562, [39] which contrasts greatly with the 72‐hour IC 50 values found for gypsogenic acid of 227.6 μM for K562 and 121.2 μM for LAMA‐84 cell [40] . This important difference in activity needs confirmation with additional studies using the same test conditions.…”
Section: Natural Pentacyclic Triterpenesmentioning
confidence: 80%
See 1 more Smart Citation
“…An interesting comparison might be made between the oleananes gypsogenin ( 5 ) and gypsogenic acid ( 6 ), whose only difference is the group on C‐4: an aldehyde and a carboxylic acid, respectively (Figure 2). Gypsogenin has presented a 24‐hour IC 50 of 12.67 μM against K562, [39] which contrasts greatly with the 72‐hour IC 50 values found for gypsogenic acid of 227.6 μM for K562 and 121.2 μM for LAMA‐84 cell [40] . This important difference in activity needs confirmation with additional studies using the same test conditions.…”
Section: Natural Pentacyclic Triterpenesmentioning
confidence: 80%
“…However, it is adequate to imagine that the group at C‐4 might play a decisive role for antileukemic activity. Furthermore, compared with cell lines of other types of leukemia, it has been shown that these Ph+ lines, K562 and LAMA‐84, have presented decreased sensitivity to gypsogenic acid [40] …”
Section: Natural Pentacyclic Triterpenesmentioning
confidence: 99%
“…A slightly modified version of MTT assay was performed to determine the cell survival fraction. 18 Exponentially growing HL-60 and HL-60/Dox cells were seeded into 96well plates. The cells were treated with the indicated drugs in 3-5 different concentrations, and the cell viability was determined after 72 hours of incubation, adding MTT (10 mg/ml).…”
Section: Mtt Assaymentioning
confidence: 99%
“…The population of the taxon has decreased as a result of the reduction of its distribution. G. trichotoma has been proved to have high anti-inflammatory, antiviral, antibacterial, antioxidant, and hepatoprotective properties [1]. Phytochemical examination revealed the presence of triterpene saponins, flavonoids, sterols, triterpenes and volatiles [2].…”
Section: Gypsophila Trichotomamentioning
confidence: 99%